Comparison of Mudskipper Tail Fin Skeleton Structure Boleophthalmus boddarti and Periophthalmus chrysospilos - Siti Yuli Nuril Hidayah; Hari Santoso; Husain Latuconsina (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2023)
Glodok fish (mudskipper) is a member of the amphibian fish group that uses its tail fin as a tool for movement, both in water and on land. The aim of this study was to compare the skeleton structure and the number of tail fin bones of Boleophthalmus boddarti and Periophthalmus chrysospilos. The sampling location is in Banyuurip Mangrove Center (BMC), Ujungpangkah District, Gresik Regency. The research was carried out in December 2020-January 2021 at the Unisma FMIPA Laboratory. The research method used is descriptive qualitative, with purposive sampling and Alizarin red staining. The results showed that there was no difference in the tail fin skeleton structure of the two species. The modification of the caudal fins of the two species was shown by widening in the second and third spine hemalis and neural spine. The number of caudal fin bones of B. boddarti is the preural centrum os, two epural bones, the parhypural os, five hypural os, and lepidotrichia with two types of fin radius, namely 3 un-segmented and unbranched fin radii and 17 radii segmented and branched. In P. chrysospilos, there are eight cenrum preural os, two epural os, parhypural os, five hypural os, and lepidotrichia with two types of caudal fin radius, namely 3 un-segmented and unbranched fingers and 14 segmented and branched fingers. Keywords: caudal fin, Boleophthalmus boddarti, Periophthalmus chrysospilos, number of bones